Myoclonus as an unusual presentation of progressive multifocal leukoencephalopathy in a HIV positive patient - Lucian Chicea; Elena Cecilia Rosca; Ovidiu Rosca; M. Ciolan; Mihaela Simu (Romanian Journal of Neurology, 2012)
From mild muscular contractions to gross jerks affecting the whole body, myoclonus is an involuntary movement caused by an excessive discharge from a group of neurons located in one or multiple sites from cortical to peripheral level. Progressive multifocal leukoencephalopathy (PML) is a rare demyelinating disease of the CNS caused by oligodendroglial destruction due to JC virus. Usually it manifests with focal neurological deficits such as motor weakness, sensory abnormalities, visual disturbances, cognitive impairments, movement disorders having a low incidence in these patients. We report a rare case of myoclonus as a neurological complication of PML in AIDS, analyzing the link between the stage of HIV infection, the MRI lesions and the type of myoclonus, being also aware of potential interactions between the antiepileptic drugs and the antiretroviral therapy.